Social delay tolerant approach for safety services in vehicular networks - Nguyen-Minh, Huong; Benslimane, Abderrahim; Radenkovic, Milena (2015)
Vehicular networks have attracted attention for recent years due to their various and emerging applications supporting secure and convenient driving. Regarding specific features of vehicular networks, we propose a new Social-aware Vehicular DTN protocol (SocVe) respectively for a type of safety applications such as emergency support services. We evaluate our protocol in short contact and intermittent connection scenarios extracting from mobility data set in Hanoi city. We conduct comparative performance evaluation of SocVe in multiple scenarios with different destination centralities against a geographical protocol.